To assess the analgesic efficacy of adjuvant magnesium sulfate added with ropivacaine over ropivacaine alone as a continuous infiltration in total abdominal hysterectomy wound: A randomized controlled trial - Devalina Goswami; Mahesh K. Arora; Karthik V. Iyer; Nageswara Rao Tangirala; Jai Bhagwan Sharma; Sunesh Kumar; Mani Kalaivani (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Magnesium sulfate (MgSO4) has been demonstrated to have analgesic property in various clinical settings. This study explores if addition of MgSO4 to ropivacaine increases its analgesic efficacy when infiltrated continuously in the postsurgical wound following total abdominal hysterectomy. Material and Methods: This randomized controlled trial was conducted at a tertiary care referral hospital in New Delhi, India. Fifty-two patients were randomized into two groups to receive the intervention of which 48 were able to complete the study. The first group (n = 26) received 0.25% ropivacaine infiltration and the second group (n = 26) received 0.25% ropivacaine with 5% MgSO4 at the incision site for 48 h postoperatively. Primary objective was to compare the total postoperative opioid (morphine) consumption by the study participants in both the groups and the secondary objectives were pain scores at rest and at movement, patient satisfaction score, and wound quality of life on the 7th postoperative day among the two groups. Results: Both the groups were comparable in their demographic characteristics. The median morphine consumed at 48 h postoperatively was 16.5 [0–77] mg in the ropivacaine group and 13[1–45] mg in the ropivacaine with MgSO4 group and the difference was statistically insignificant (P = 0.788). There was no statistical difference between the groups with respect to the pain scores, patient satisfaction, or wound quality of life at 7 days. Conclusion: The addition of MgSO4 to ropivacaine does not confer any additional postoperative analgesic benefits over ropivacaine alone in continuous wound infiltration following total abdominal hysterectomy.